Association of Contribution and Adequacy Levels of Energy and Nutrients from Supplementary Foods with Perceived Breast Milk Sufficiency among Lactating Mothers in a Stunting Prevention Program - Hafika Yunisari Pradina; Katrin Roosita; Ahmad Sulaeman; Hardinsyah Hardinsyah; Stefanus Indrayana (Journal of Health and Nutrition Research, 2026)
Maternal nutrition intake, as well as nutritional status, influence breast milk production and nutrient content. To reduce stunting, the GAS KIPAS Stunting Program (Gerakan Anak Sehat – Kolaborasi Inklusif Pengusaha Indonesia Atasi Stunting) provided high-nutrient supplementary foods for lactating mothers. This program was implemented in several priority locations. This study analyzed the associations between contribution and the adequacy levels of energy and nutrients from supplementary foods with perceived breast milk sufficiency. Secondary data were obtained from the 2023 GAS KIPAS Stunting Program. This study used a one-group pretest–posttest pre-experimental design without a control group. Nutritional intake of supplementary foods was obtained using the Comstock method. Statistical analyses included the Wilcoxon signed-rank test and Spearman's rank correlation. The results showed no significant association between the energy and nutrient contribution of supplementary foods and perceived breast milk sufficiency. However, calcium adequacy level showed a significant positive correlation (r=0.38; p=0.039). During lactation, mothers require increased micronutrient intake to support maternal health and infant development. Conclusion: Providing supplementary foods for lactating mothers does not directly affect mothers’ perceptions. These findings suggest that a larger sample size, measurement of milk production volume, and a 24-hour food recall may be needed to optimize intervention outcomes in supporting exclusive breastfeeding as a stunting prevention